(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Traditional postharvest loss reduction methods encompass indigenous, low-cost practices designed to limit avoidable quantity and quality losses of tomatoes within environments where cold chain infrastructure is underdeveloped. Severe physiological deterioration frequently causes substantial financial attrition for smallholders in Benue State, necessitating an evaluation of how cooperative frameworks utilise local preservation techniques. The primary objective of the study was to examine traditional postharvest loss reduction methods among tomato cooperative farmers in Benue State, Nigeria. A descriptive survey research design was adopted, utilizing a structured questionnaire to collect data from a sample of 381 registered cooperative farmers, with 343 valid responses retrieved for analysis. Data were analysed using descriptive statistics and multiple regression analysis via SPSS version 27.0. Results for the first hypothesis indicated that socioeconomic characteristics exert a statistically significant influence on traditional postharvest practices, yielding an R value of 0.612, an R Square of 0.375, and a p value of 0.000 (F = 204.286). Analysis of the second hypothesis revealed that traditional storage methods significantly impact the shelf-life extension of tomatoes, supported by an R value of 0.548, an R Square of 0.300, and a p value of 0.000 (F = 146.183). Findings suggested that while human capital factors like education and experience enhance handling competence, low-cost systems such as ventilation and sun-drying remain indispensable buffers against spoilage in rural settings. The study concluded that economic survival in the regional tomato value chain depends on the synergy between farmer attributes and indigenous preservation technologies. Recommendations included the organisation of regular peer-to-peer training sessions by cooperative leaders and the promotion of improved ventilated storage structures by agricultural extension agencies to mitigate quantitative stock losses.